The Stationarity of South Asian Real Exchange Rates Allowing for Structural Breaks - Ariful Hoque; Rajabrata Banerjee (Australasian Accounting, Business and Finance Journal, 2014)
After the introduction of the nonlinear unit root test in 2003, research has provided evidence of nonlinear real exchange rate dynamics in Asian countries. However, few studies have conducted nonlinear unit root tests for South Asian real exchange rates. Some of these studies argued in favour of stationary real exchange rates, whereas others concluded the nonstationarity of real exchange rates. A major problem with these nonlinear unit root tests is their failure to consider structural changes for long periods of time. To confirm the mixed test results for the stationarity of South Asian real exchange rates, this study employs unit root test by allowing both single and multiple endogenous structural breaks for Bangladesh, India, Pakistan and Sri Lanka for the period of 1957 to 2011, except that data for Bangladesh covers a shorter sample period. Results show nonstationary real exchange rates for the sample countries. Overall empirical evidence indicates that long-run purchasing power parity does not hold for major South Asian countries.
Keywords: stationary; nonlinear; unit root; structural break; purchasing power parity